WAR AND SOCIO-ECONOMIC DEVELOPMENT - Riak PhD, Dr. Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The literature on the study of war on economic condition of a country is very limited however a brief review of the available literature is presented below. Bloomberg et al. (2002) present an economic model of war, in which terrorist groups who are unhappy with the current situation in a country try to bring change by indulging in terrorist activities. Terrorist activities of such groups may have different results depending on the economic situation. Either they can reduce the economic activities by increasing war, or if more economic incentives are present in the economy then war is reduced for example, more employment opportunities can reduce the incentive to indulge in terrorist activities. Study is of the view that recessions in high income countries can result in higher probability of terrorist activities.